Semantics, culture, and cognition : universal human concepts in culture-specific configurations - Wierzbicka, Anna (Oxford University Press, 1992)
To what extent are languages 'essentially the same'? Is every word in our language translatable into every other language or are some of our words and concepts 'culture specific'? In this innovative study, Wierzbicka ranges across a wide variety of languages and cultures, attempting to identify concepts which are truly universal, while at the same time arguing that every language constitutes a different 'guide to reality'. The lexicons of different languages, she shows, do indeed suggest different conceptual universes. Not everything that can be said in one language can be said in another, and this is not just a matter of certain things being easier to say in one language than in another. In the development of her argument, Wierzbicka focuses on the words for emotion, moral concepts, names, and titles.